Peran Koperasi Kemuning Mitra Persada dalam Pengembangan UMKM di Pematangsiantar - Romario F D Purba; Albenopri Simarmata; Dian G Purba; Rafael E J Siregar; Monika Siallagan; Yosi I Saragih; Rizky Sahertian; Muhammad Fauzi (Asosiasi Riset Ekonomi dan Akuntansi Indonesia, 2025)
MSME players or those who will establish a business sometimes experience difficulties in providing business capital, even though MSMEs are one of the driving forces of the economy in Indonesia, especially for small and medium communities. Cooperatives are one of the solutions for loan providers, especially for MSME players or those who will enter the world of MSMEs, because the system is flexible and uncomplicated. This research aims to see the efforts of Kemuning Mitra Persada Cooperative in developing MSMEs in Pematangsiantar. This research uses a qualitative analysis approach, where data collection techniques are carried out by interviewing the Kemuning Mitra Persada Cooperative.